2017
DOI: 10.1038/aps.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure enhances oral plasma exposure of zidovudine in rats by downregulation of hepatic UGT2B7 and intestinal P-gp

Abstract: HIV infection is often associated with liver failure, which alters the pharmacokinetics of many drugs. In this study we investigated whether acute liver failure (ALF) altered the pharmacokinetics of the first-line anti-HIV agent zidovudine (AZT), a P-gp/BCRP substrate, in rats. ALF was induced in rats by injecting thioacetamide (TAA, 300 mg·kg·d, ip) for 2 days. On the second day after the last injection of TAA, the pharmacokinetics of AZT was investigated following both oral (20 mg/kg) and intravenous (10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Another experimental model of ALF, i.e., thioacetamide-induced liver failure, confirms observations from CCl 4 -treated rats, as significant downregulation of intestinal P-gp expression was observed. The study provided also functional confirmation of the observed changes in transporter level, since ALF significantly elevated rhodamine-123 intestinal absorption, without affecting intestinal integrity in in vivo study, which points out on deterioration of intestinal P-gp function [ 30 ].…”
Section: Liver Failurementioning
confidence: 74%
See 1 more Smart Citation
“…Another experimental model of ALF, i.e., thioacetamide-induced liver failure, confirms observations from CCl 4 -treated rats, as significant downregulation of intestinal P-gp expression was observed. The study provided also functional confirmation of the observed changes in transporter level, since ALF significantly elevated rhodamine-123 intestinal absorption, without affecting intestinal integrity in in vivo study, which points out on deterioration of intestinal P-gp function [ 30 ].…”
Section: Liver Failurementioning
confidence: 74%
“…Experimental studies in rats with thioacetamide-induced ALF revealed mild, 1.6-fold (statistically not significant) upregulation of BCRP in liver failure [ 30 ].…”
Section: Liver Failurementioning
confidence: 99%
“…Metabolic, mitochondrial, renal and hepatic toxicity together with overall clinical safety issues have been attributed to antiretrovirals used for HIV management, including PIs, NRTIs and NNRTIs, due to off target interferences with physiological pathways [6,8,9,16,[39][40][41]. Entry and integrase inhibitors are supposed to be safer and free of these toxicities, however there is lack of evidence of in vivo studies [21].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments carried out mostly in Caco-2 cells (human colon carcinoma cell line) suggest downregulation of the expression and function of ABCB1/P-gp. Exposure of the cells to plasma from animals with acute liver failure (ALF) induced by administration of carbon tetrachloride (CCl4) [51] and thioacetamide [52] proved its significantly greater inhibitory potency on P-gp-mediated rhodamine-123 transport across Caco-2 cell monolayers than plasma from control rats. Contrary to significant reduction in P-gp levels, the plasma from thioacetamide-induced ALF rats did not produce a significant impact on Caco-2 expression of BCRP [52].…”
Section: In Vitro Studiesmentioning
confidence: 99%